One to Many: A Framework for Scaling Risk Mitigation Assurance - Bigley, Joel (Edelweiss Applied Science and Technology, 2018)
The lack of vulnerability control leads to organizational harm in global businesses when the exploitation of a weakness occurs. How can a global supply chain protect itself from vulnerabilities that can damage their brand and their physical property? In this qualitative case study the author shows how a multi-site corporation can use a method to learn what the vulnerabilities are in a single facility and use a framework to methodically scale the controls needed to mitigate vulnerabilities across the supply chain. This framework allows leadership to keep cost in mind so that the highest vulnerabilities are mitigated as a priority. A team of security experts was used to capture data in framework used for analysis. This framework was then used strategically to reduce the overall risk of threat vectors in the global organization.